NGARUH STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN PADA SUB SEKTOR PULP AND PAPER YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2010 – 2014 - Gea Brigita; Lena Farida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to determine the effect of capital structure on Pulp and Paper Sector Sub listed on the Indonesia Stock Exchange (BEI) study period of 2010 - 2014. The capital structure is used as independent variables, Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), Longterm Debt to Assets Ratio (LDAR), Longterm Debt to Equity Ratio (lder). While that is used as the dependent variable is the value of the company is Price Earning Ratio (PER). The method used to observe the effect of capital structure to the company's value is by using multiple linear regression.This study uses secondary data from the financial statements of companies sampled and sampling using purposive sampling techniques. Classic assumption test in this study include normality test, multicollinearity, heterocedasticity test, autocorrelation test. Analysis of data using the multiple linear regression analysis, t-test, f, and test the coefficient of determination. Analysis of data using multiple linear regression analysis with SPSS 16.The results showed that the variables DAR partially (t test) significantly affects the value of the company on the subsector of pulp and paper listed in the Indonesia Stock Exchange (BEI), while the variable DER, LDAR, lder no significant effect on the capital structure on a sub-sector of pulp and paper listed in the Indonesia Stock Exchange (BEI). The results of the study simultaneously (f test) showed a significant effect of the variable DAR, DER, LDAR, lder on firm value in pulp and paper subsectors listed in the Indonesia Stock Exchange (BEI). Keywords: Capital Structure, Corporate Values, DAR, DER, LDAR, LDER